2008
DOI: 10.1111/j.1875-595x.2008.tb00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries assessment by clinical examination with or without radiographs of young Chinese adults

Abstract: Due to the significant number of clinically undetected carious cavities in these young Chinese adults who live in a community with water fluoridation, it may be advisable to use a correction factor to adjust the caries experience obtained from epidemiological surveys when bitewing radiographs are not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…While the findings of this study support those of other recent studies [Poorterman et al, 2002;Hopcraft and Morgan, 2005;Lillehagen et al, 2007;Chu et al, 2008] in respect of the general underestimation of carious lesions where radiographic diagnosis is not used, they build on those studies in the presentation of more detailed data on its nature and intra-oral distribution (as represented by the information in table 3 ). That the discrepancy was considerably greater for approximal surfaces than for occlusal surfaces both confirms and extends earlier findings and again underlines the need for bitewing radiographs to be a routine part of oral epidemiological surveys (and, of course, the clinical management of patients) wherever logistics and funding permit.…”
Section: Discussionsupporting
confidence: 77%
“…While the findings of this study support those of other recent studies [Poorterman et al, 2002;Hopcraft and Morgan, 2005;Lillehagen et al, 2007;Chu et al, 2008] in respect of the general underestimation of carious lesions where radiographic diagnosis is not used, they build on those studies in the presentation of more detailed data on its nature and intra-oral distribution (as represented by the information in table 3 ). That the discrepancy was considerably greater for approximal surfaces than for occlusal surfaces both confirms and extends earlier findings and again underlines the need for bitewing radiographs to be a routine part of oral epidemiological surveys (and, of course, the clinical management of patients) wherever logistics and funding permit.…”
Section: Discussionsupporting
confidence: 77%
“…13 In everyday clinical practice, radiographic evaluation is usually limited to teeth in doubt for caries or routinely carried out in subjects at high risk of caries, increasing the probability of detecting a lesion, leading to a high specificity and low sensitivity. 25 Instead, the near-infrared light transillumination might be used routinely over all surfaces particularly approximal surfaces, with no side effect, with an estimated high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…One conventional diagnostic method relies on the radiolucency of hidden caries, which makes it detectable in a radiograph. Indeed, a clinical study of 200 young adults found that clinical evaluation with bitewing radiographic examination detected 106% more caries, mainly in the proximal surfaces, in the posterior permanent teeth than by clinical evaluation alone [8], which suggested that the detection rate of hidden caries depends on the prevalence of caries in the population and the frequency of bitewing radiographic examinations [24]. Although routine use of bitewing radiography could help identify teeth with hidden caries to allow early and conservative treatment, it is inaccurate in diagnosing occlusal enamel caries [19], and its detection rate for occlusal lesions is less than 50% of that for histological sectioning [30].…”
Section: Introductionmentioning
confidence: 99%